2014
DOI: 10.1111/pan.12480
|View full text |Cite
|
Sign up to set email alerts
|

Clinical anatomy of the maxillary nerve block in pediatric patients

Abstract: Anatomical landmarks in children are mostly extrapolated from studies in adults. Despite this, complex regional anesthetic procedures are frequently performed on pediatric patients. Sophisticated imaging techniques are available but the exact position, course and/or relationships of the structures are best understood with appropriate anatomical dissections. Maxillary nerve blocks are being used for peri-operative analgesia after cleft palate repair in infants. However, the best approach for blocking the maxill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
(18 reference statements)
1
15
0
Order By: Relevance
“…It is simple, reliable and an almost risk-free approach for children with effective and prolonged analgesia [8]. Anesthesiologists can reach the maxillary nerve after its emergence from the foramen rotundum, within the pterygopalatine fossa before it branches to innervate the palate [9].…”
Section: Original Articlementioning
confidence: 99%
“…It is simple, reliable and an almost risk-free approach for children with effective and prolonged analgesia [8]. Anesthesiologists can reach the maxillary nerve after its emergence from the foramen rotundum, within the pterygopalatine fossa before it branches to innervate the palate [9].…”
Section: Original Articlementioning
confidence: 99%
“…[15][16][17][18] Among all types of approach, the suprazygomatic approach has been reported to have a more favourable safety profile. 2,4,19,21 While some of the complications are related to the particular anatomical approach used, others are related to the volume of anesthetic injected into the pterygopalatine fossa (PPF). The average volume of the PPF in adults has been reported from studies in dry skulls as close to one mL.…”
Section: Résultatsmentioning
confidence: 99%
“…The location of the pterygopalatine ganglion, and the maxillary nerve and its branches are projected onto the surface bony anatomy in yellow. The pixelated box is located at the level of the orbital cavity Prigge et al, 21 the plane perpendicular to the median plane was considered to be 0°(utilizing the anterior and superior view). If the needle was angled superiorly (in the anterior view) or anteriorly (in the superior view) towards the PPF, it was considered an increase (?)…”
Section: Block Target and Techniquementioning
confidence: 99%
“…A cadaveric study (Prigge et al, ) investigated for the first time in the pediatric population the most effective technique for the maxillary nerve blockade used for congenital cleft palate repair. From findings derived from measuring pediatric skulls and cadavers (0–1 year old), the study concluded a commonly described suprazygomatic approach to be most effective due to its easily palpable landmarks.…”
Section: Resultsmentioning
confidence: 99%